2016
DOI: 10.1371/journal.pone.0159083
|View full text |Cite|
|
Sign up to set email alerts
|

Risk Factors for Bovine Tuberculosis (bTB) in Cattle in Ethiopia

Abstract: Bovine tuberculosis (bTB) infection is generally correlated with individual cattle’s age, sex, body condition, and with husbandry practices such as herd composition, cattle movement, herd size, production system and proximity to wildlife—including bTB maintenance hosts. We tested the correlation between those factors and the prevalence of bTB, which is endemic in Ethiopia’s highland cattle, in the Afar Region and Awash National Park between November 2013 and April 2015. A total of 2550 cattle from 102 herds we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
49
4
6

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 59 publications
(80 citation statements)
references
References 51 publications
7
49
4
6
Order By: Relevance
“…Our study revealed the risk of having bTB to be significantly associated with the age of the animal. This finding agrees with the published observations made elsewhere in Africa (Dejene et al, 2016;Egbe et al, 2016). From our findings, female animals appear to have a higher risk of infection than males, similar to the findings of Worku et al (2016) in Ethiopia.…”
Section: Discussionsupporting
confidence: 93%
“…Our study revealed the risk of having bTB to be significantly associated with the age of the animal. This finding agrees with the published observations made elsewhere in Africa (Dejene et al, 2016;Egbe et al, 2016). From our findings, female animals appear to have a higher risk of infection than males, similar to the findings of Worku et al (2016) in Ethiopia.…”
Section: Discussionsupporting
confidence: 93%
“…Consistent with other studies livestock keeping activities that were associated with bTB transmission to cattle involved uncontrolled movement of animals and introduction of animals into a herd without bTB pre-testing for social benefit, cultural or commercial purpose [7,15,3537]. The free movement of cattle in communal farming within the village parameters is a common practice and movement to areas adjacent or into game reserves in search of pasture was attributed to the frequent drought conditions in the area.…”
Section: Discussionsupporting
confidence: 70%
“…Due to an increase in land use there is infringement of human activities into conservation areas that results in the sharing of natural resources with wildlife [14]. Studies in other countries have suggested that transmission of bTB to cattle from wildlife occurs either through direct contact at shared resources such as watering points or indirectly, when cattle graze on contaminated pastures [15]. Therefore, the wildlife-livestock interface has been defined as a high-risk area for bTB transmission from wildlife to cattle [16].…”
Section: Introductionmentioning
confidence: 99%
“…During such interactions, competition of livestock with wild grazers for pasture and water, predation of livestock by large carnivores, and transmission of zoonotic diseases between domestic and wild animals occur (Dejene et al 2016). According to previous studies (Prins 2000;Georgiadis et al 2007), competition for scarce grazing and water resources causes conflicts between pastoralists and wildlife managers, since pastoralists and agro-pastoralists migrate into the vicinity of national parks and protected areas during prolonged drought periods in semi-arid rangelands of Eastern Africa.…”
Section: Introductionmentioning
confidence: 99%